Demystifying Králík - Kosák , Michal (Dějiny – teorie – kritika, 2011)
The contribution by Oldřich Králík to Mácha’s textology has been interpreted one-sidedly since the polemics in 1954-1955. The author in his polemics critically examines the study by Michal Charypar K textologickým sporům o Máchovo dílo [On the Textological Disputes on Mácha’s Work], which in his opinion appears rather as a ‘direct’ and engaged participant in this dispute. According to Kosák, it is necessary to construct a new view of the given dispute based on the archival materials, through whose analysis he attempts to document the nature of Králík’s research on Mácha (primarily in 1950–1954) and his stimuli to the edition of Mácha’s Treatises in the Library of Classics in more detail and not one-sidedly.